MULTIPLICATION AND DIVISION LEARNING ASSISTANCE USING THE FUN LEARNING METHOD ASSISTED BY RECYCLING TEACHING AIDS AT KOBER BINA WARGA MEKARJAYA - Emas Marlina; Windra Tasya Mahesa; Ade Rukmana Julianti; Neneng Bernika Cahayati (Universitas INABA, 2023)
Education is instrumental in shaping individuals and societies, with mathematics education serving as the foundation for critical thinking and problem-solving skills. Understanding multiplication and division concepts is crucial for young learners, as it provides the groundwork for advanced mathematical concepts. To enhance the learning experience and make it enjoyable, innovative teaching methods and creative teaching aids are essential. This abstract focuses on the implementation of a fun learning method, supported by recycling teaching aids, for multiplication and division learning assistance at Kober Bina Warga Mekarjaya. Kober Bina Warga Mekarjaya is a renowned educational institution committed to providing quality education to young learners. Recognizing the importance of engaging teaching techniques, the institution has adopted a fun learning approach to enhance students' understanding of multiplication and division. This approach integrates playfulness and creativity into the learning process, fostering an enjoyable environment and facilitating a deeper comprehension of mathematical concepts. One innovative strategy employed in this learning approach is the use of recycling teaching aids. These aids are created from recyclable materials, promoting sustainability and environmental awareness among students. By incorporating recycling into the learning process, students not only gain mathematical knowledge but also develop a sense of responsibility toward the environment. This approach encourages active engagement and nurtures ecological consciousness among young learners.